Hard to Kill: Jane Smith #2 - Patterson, James ([Place of publication not identified] : Little Brown and Company, 2024)
"Attorney Jane Smith is mounting an impossible criminal defense. Her client, Rob Jacobson, is the unluckiest of the lucky. No sooner is he accused of killing a family of three in the Hamptons than a second family is gunned down. It's not double jeopardy. It's not double murder. It's double triple homicide. Jane's career has spanned from NYPD beat cop to Hamptons courtroom. She's tough to beat. She's even tougher to kill. The defense may never rest."--Publisher's description.
new book 2024 summer.
Keywords: Smith, Jane; Trials (Murder); Women lawyers; FICTION / Thrillers; Criminal defense lawyers; Legal stories; Detective and mystery fiction; Terminally ill